La problemática de la racionalidad y la bioética - Roberto Estrada Olguín (Universidad Autónoma de Ciudad Juárez, 2012)
The understanding of the "science", "philosophy" and "morality" depends to some extent for the understanding of the rationality, then is clear that the fundamental problem is: what are the fundamentals that have several "philosophies" to provide what the rational is? This paper exposed a philosophic perspective of the problem of rationality in bioethics and this exposition we divide into three sections: first describe a brief history of bioethics and the scope of this discipline. Secondly, we develop the issue of rationality under Nicolas Rescher, and the end, we exposed two ethics alternatives for the bioethics: 1) the Aristotelian phronesis and 2) the Kantian categorical imperative, which the rationality plays a different role.